Tetrandrine inhibited chronic "inflammatory" pulmonary hypertension in rats - Wang Huai-Liang; Zhang Xin-Hua; Jin Xin; Xing Jun; Zhang Dao-Rong (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of tetrandrine (Tet), on pulmonary hypertension. METHODS: An ""inflammatory"" chronic pulmonary hypertension induced by monocrotaline (Mon) in rats was used. RESULTS: Tet 50, 100, and 150 mg.kg-1.d-1 i.g. 3 wk inhibited Mon-induced increase of pulmonary artery pressure (PAP) by 23.8%, 34.9% (P < 0.05), and 42.0%, (P < 0.05); the right heart index by 2.0%, 25.0%, and 30.0% (P < 0.05) respectively compared with those from Mon group, without significant influence on the systemic artery pressure (SAP). Using histological exam by Verhoeff elastic stain and computer scanning analysis, it was found that Tet (100 mg.kg-1.d-1) for 3 wk, inhibited the increase of medial thickness and cross sectional area by 57.8% (P < 0.01) and 54.6% (P < 0.01), respectively vs Mon group. CONCLUSION: Tet ameliorated the development of pulmonary vascular and lung tissue injury induced by Mon in rats.